1995
DOI: 10.1093/oxfordjournals.annonc.a059115
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial of vinorelbine and thiotepa in metastatic breast cancer

Abstract: The present study has shown this combination to be active as second-line treatment, and its toxic effects have been well tolerated. It should be considered a reasonable option for patients with metastatic disease who have already been treated with anthracyclines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
7
0

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 1 publication
2
7
0
Order By: Relevance
“…a substantial activity for combination regimens including this agent would be anticipated. and preliminary results seem to confirm these expectations (Scheithauer et al 1993: Spielmann et al 1994: Fabi et al 1995: Nole et al 1995: Kornek et al 1996.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…a substantial activity for combination regimens including this agent would be anticipated. and preliminary results seem to confirm these expectations (Scheithauer et al 1993: Spielmann et al 1994: Fabi et al 1995: Nole et al 1995: Kornek et al 1996.…”
supporting
confidence: 57%
“…substantial activity for combination regimens including this agent would be anticipated. Among several such combination regimens that have alreadv been investigated in patients with advanced breast cancer (Scheithauer et al 1993: Spielmann et al 1994: Fabi et al 1995: Nole et al 1995: Kornek et al 1996. the combination of vinorelbine and doxorubicin has probably shown the most promising activitv: there was a relatively hiah rate of cardiotoxicitv (10%7) however.…”
Section: Discussionmentioning
confidence: 99%
“…In all of these studies, treatment was well tolerated, with neutropenia being the most frequent and dose-limiting toxicity. Based on these results and documented activity of single-agent vinorelbine in second-line chemotherapy (Gasparini et al, 1994;Degardin et al, 1994), a substantial activity for combination regimens including this agent would be anticipated, and preliminary results seem to confirm these expectations (Spielmann et al, 1994;Fabi et al, 1995;Nole et al, 1995).…”
mentioning
confidence: 82%
“…(Cannabbio et al, 1989;Garcia-Conde et al, 1992;Romero et al, 1994;Toussaint et al, 1994;Fumoleau et al, 1994), substantial activity for combination chemotherapy including this agent would be anticipated. Among several different such combination regimens that have been investigated in advanced breast cancer (Spielmann et al, 1994;Fabi et al, 1995;Nole et al, 1995), the combination of vinorelbine and doxorubicin has shown the most promising activity, although there was a relative high rate of cardiotoxicity (10%) resulting in three (4%) treatmentassociated toxic deaths (Spielmann et al, 1994).…”
Section: Survivalmentioning
confidence: 99%
“…Efficacy and tolerance of vinorelbine were investigated in patients with metastatic breast carcinoma (MBC), with encouraging results, in several studies of first-or secondline therapy alone [1][2][3], and in combination with other drugs [4][5][6]. The effectiveness of 5-fluorouracil (5FU) in adenocarcinomas is well known [7].…”
mentioning
confidence: 99%